Juvenile toxicity study of PF‐07256472/recifercept, a recombinant human soluble fibroblast growth factor receptor 3, in 2–3‐month‐old cynomolgus monkeys. Issue 3 (11th November 2022) - Campion, Sarah N.; Bowman, Christopher J.; Fuchs, Antje; Karanian, David; Rana, Payal; Cappon, Gregg D.
Abstract: Achondroplasia is an autosomal disorder caused by point mutation in the gene encoding fibroblast growth factor receptor 3 (FGFR3) and resulting in gain of function. Recifercept is a potential disease modifying treatment for achondroplasia and functions as a decoy protein that competes for ligands of the mutated FGFR3. Recifercept is intended to restore normal bone growth by preventing the mutated FGFR3 from negative inhibitory signaling in pediatric patients with achondroplasia. Here we evaluated the potential effects of twice weekly administration of recifercept to juvenile cynomolgus monkeys (approximately 3‐months of age at the initiation of dosing) for 6‐months. No adverse effects were noted in this study, identifying the high dose as the no‐observed‐adverse‐effect‐level and supporting the use of recifercept in pediatric patients from birth. Considering that juvenile toxicity studies in nonhuman primates are not frequently conducted, and when they are conducted they typically utilize animals ≥9 months of age, this study demonstrates the feasibility of executing a juvenile toxicity study in very young monkeys prior to weaning.